Selling 'em by the Sack : White Castle and the Creation of American Food. - Hogan, David G. (NYU Press, 1997)
In the wake of World War I, the hamburger was still considered a disreputable and undesirable food. Yet by 1930 Americans in every corner of the country accepted the hamburger as a mainstream meal and eventually made it a staple of their diet. The quintessential "American" food, hamburgers have by now spread to almost every country and culture in the world. But how did this fast food icon come to occupy so quickly such a singular role in American mass culture?. In Selling 'em By the Sack, David Gerard Hogan traces the history of the hamburger's rise as a distinctive American culinar.